User Generated Highlight System for Baseball Games with Social Media Activities - Seo, Dongmahn; Ko, Heedong; Park, Hogun; Kim, Suhyun (2014 IEEE INTERNATIONAL CONFERENCE ON CONSUMER ELECTRONICS (ICCE), 2014)
In this paper, we propose a user-generated baseball highlight system. The proposed system provides environments for baseball highlight generation based on real-time text scoreboard with social media and live media. The proposed system creates short baseball highlights according to analysis of live baseball text scoreboard and social media. Users can generate baseball highlights with selections of short highlight clips.